Reviewing Violence against Women from the Perspective of the Quran - Hossein Bostan; Reza Dehghannejad (پژوهش نامه معارف قرآنی, 2017)
This article examines the issue of violence against women from the perspective of the Quran. Firstly, the most important Quranic evidence of disagreeing with violence against women focusing on the verses related to good treatment with wives, rejecting damage (Dirar), putting pressure on women, honor accusation (qazf), oath to leaving the bed (Ila’), dismissal from the home, burring alive, and inheritance of women were analyzed. The results showed that the Quran has not confirmed any cases of violence against women. The only case that may be considered as evidence of confirming violence against women is the verse of disobedience (Noshooz) that, with a more accurate reflection, it should be detected that it is not a matter of violence against women, but of a legal penalty which husband, not as a husband but as a law actor conditionally applies it and which can remove disobedience with the lowest cost. However, in the absence of any of the conditions, the husband’s violence is forbidden and considered as a crime.